A highly hemocompatible erythrocyte membrane-coated ultrasmall selenium nanosystem for simultaneous cancer radiosensitization and precise antiangiogenesis. Issue 29 (10th July 2018) - Liu, Ting; Shi, Changzheng; Duan, Linqi; Zhang, Zehang; Luo, Liangping; Goel, Shreya; Cai, Weibo; Chen, Tianfeng
Abstract : Herein we design a highly hemocompatible erythrocyte membrane-coated ultrasmall selenium nanosystem for simultaneous cancer radiosensitization and precise antiangiogenesis. Abstract : Radiotherapy is a vitally important strategy for clinical treatment of malignant cancers. Therefore, rational design and development of radiosensitizers that could enhance radiotherapeutic efficacy has attracted tremendous attention. Antiangiogenic therapy could be a potentially effective strategy to regulate tumor growth and metastasis since angiogenesis plays a pivotal role in tumor growth, invasion and metastasis to other organs. Herein, we have rationally designed a smart and effective nanosystem by combining ultrasmall selenium nanoparticles and bevacizumab (Avastin™, Av), for simultaneous radiotherapy and antiangiogenic therapy of cancer. The nanosystem was further coated with red blood cell (RBC) membranes to develop the final construct, RBCs@Se/Av. The RBC membrane coating effectively prolongs the blood circulation time and reduces the elimination of the nanosystem by autoimmune responses. As expected, RBCs@Se/Av, when irradiated with X-rays demonstrated potent anticancer and antiangiogenic responses in vitro and in vivo, as evidenced by the strong inhibition of A375 tumor growth in nude mice, without causing any obvious histological damage to the non-target major organs. Taken together, this study demonstrates an effective strategy for the design of a smart Se-based nanosystem decorated with the RBC membrane for simultaneous cancer radiosensitization and precise antiangiogenesis.